Methylation of SOCS3 is inversely associated with metabolic syndrome in an epigenome-wide association study of obesity. Issue 9 (1st September 2016) - Ali, Omar; Cerjak, Diana; Kent, Jack W.; James, Roland; Blangero, John; Carless, Melanie A.; Zhang, Yi
ABSTRACT: Epigenetic mechanisms, including DNA methylation, mediate the interaction between gene and environment and may play an important role in the obesity epidemic. We assessed the relationship between DNA methylation and obesity in peripheral blood mononuclear cells (PBMCs) at 485, 000 CpG sites across the genome in family members (8-90 y of age) using a discovery cohort (192 individuals) and a validation cohort (1, 052 individuals) of Northern European ancestry. After Bonferroni-correction ( P α=0.05 = 1.31 × 10 −7 ) for genome-wide significance, we identified 3 loci, cg18181703 ( SOCS3 ), cg04502490 ( ZNF771 ), and cg02988947 ( LIMD2 ), where methylation status was associated with body mass index percentile (BMI%), a clinical index for obesity in children, adolescents, and adults. These sites were also associated with multiple metabolic syndrome (MetS) traits, including central obesity, fat depots, insulin responsiveness, and plasma lipids. The SOCS3 methylation locus was also associated with the clinical definition of MetS. In the validation cohort, SOCS3 methylation status was found to be inversely associated with BMI% ( P = 1.75 × 10 −6 ), waist to height ratio ( P = 4.18 × 10 −7 ), triglycerides ( P = 4.01 × 10 −4 ), and MetS ( P = 4.01 × 10 −7 ), and positively correlated with HDL-c ( P = 4.57 × 10 −8 ). Functional analysis in a sub cohort (333 individuals) demonstrated SOCS3 methylation and gene expression in PBMCs were inversely correlated ( P = 2.93 × 10 −4 ) and expression of SOCS3 was positively correlated with status of MetS ( P = 0.012). We conclude that epigenetic modulation of SOCS3, a gene involved in leptin and insulin signaling, may play an important role in obesity and MetS.